Assessing the impact of medication adherence on health outcomes in pediatric patients with chronic diseases - Nanda, Naimish; Ali Syed Sabir Ali, Syed Sajid (Journal of Neonatal Surgery, 2025)
Children's prescription non-adherence is a challenging problem for the healthcare system. This problem may be influenced by the child's age, lack of knowledge about the illness or its treatment, culture, family dynamics, financial situation, drug use, and preferences. The most effective practices may focus on well-defined mediations for each patient and their family members. Drug specialists are at the forefront of patient care and can help patients take their drugs more consistently by providing guidance and building a trustworthy relationship with the family. This article discusses frequent adherence issues with children’s chronic diseases and offers some methods to improve adherence. Pharmacotherapy is frequently used over an extended period of time to treat chronic disorders. Approximately 50% of patients do not take their prescriptions as recommended, so even while these drugs are effective at fighting disease, their full advantages are sometimes not realized. Poor drug adherence can be caused by a wide range of factors, including those pertaining to individuals, doctors, and health care systems. The complexity and diversity of drug adherence hurdles necessitate multifaceted approaches to adherence improvement.